Bark beetles as agents of change in social–ecological systems. (16th January 2018) - Morris, Jesse L; Cottrell, Stuart; Fettig, Christopher J; DeRose, R Justin; Mattor, Katherine M; Carter, Vachel A; Clear, Jennifer; Clement, Jessica; Hansen, Winslow D; Hicke, Jeffrey A; Higuera, Philip E; Seddon, Alistair WR; et al.
Abstract : Due to recent outbreaks of native bark beetles, forest ecosystems have experienced substantial changes in landscape structure and function, which also affect nearby human populations. As a result, land managers have been tasked with sustaining ecosystem services in impacted areas by considering the best available science, public perceptions, and monitoring data to develop strategies to suppress bark beetle epidemics, and in some cases to restore affected lands and ecosystem services. The effects of bark beetle outbreaks are often detrimental to the provision of ecosystem services, including degraded landscape aesthetics and diminished air and water quality. However, there have been instances where bark beetle outbreaks have benefited communities by, for example, improving habitat for grazing animals and enhancing real‐estate values. As a consequence of the interaction of a warming climate and susceptible forest stand conditions, the frequency, severity, and extent of bark beetle outbreaks are expected to increase and therefore will continue to challenge many social–ecological systems. We synthesize experiences from recent outbreaks to encourage knowledge transfer from previously impacted communities to potentially vulnerable locations that may be at risk from future bark beetle epidemics.